Preparation method of laser cladding in-situ synthesis Al2O3 ceramic reinforced high-entropy alloy coating doped with trace B
The preparation method for in-situ self-generated Al2O3 ceramic enhanced high-entropy alloy coating is solved by laser cladding with trace B, and the performance problem of high entropy alloy coating in extreme environments is improved, and high hardness, wear resistance and high temperature oxidation resistance are improved.
Patent Information
- Application Number
- CN202411924447.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-entropy alloy coatings show insufficient hardness, wear resistance and high-temperature oxidation resistance in extreme environments, and the coating has defects such as pores, microcracks and inclusions, which affect its binding strength and stability.
The preparation method for in-situ self-generated Al2O3 ceramic enhanced high-entropy alloy coating is adopted for laser cladding with trace amounts of B. By mixing the powders of Al, Ti, Cr, Fe, V and B in a specific molar ratio, ball milling and drying, it is pre-installed on the surface of the titanium alloy substrate and laser cladding is performed to form a high-entropy alloy coating.
The high hardness, excellent wear resistance and high temperature oxidation resistance of the high entropy alloy coating are achieved, which reduces the defects and embrittlement problems of the coating, improves the bonding strength with the substrate, and enhances the overall performance of the coating.
Smart Images

Figure CN119710678A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser surface modification of titanium alloys, and in particular to a method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B. Background Art
[0002] In the field of materials science and engineering, titanium and its alloys are widely used in aerospace, chemical industry, medical and other fields due to their excellent mechanical properties, good corrosion resistance and biocompatibility. However, the application of pure titanium and traditional titanium alloys in certain extreme environments is limited, such as high-temperature oxidation environments or severe wear. Therefore, the development of surface modification technologies with higher performance, such as the preparation of surface coatings, has become the key to improving the application range of titanium-based materials.
[0003] High entropy alloy (HEA) is a new type of material that has developed rapidly in recent years. Since it was proposed by Yeh et al. in 2004, it has attracted widespread attention for its excellent low-temperature toughness, thermal stability, wear resistance, corrosion resistance and other properties. It is the preferred material for preparing surface coatings of titanium-based materials.
[0004] At present, the main preparation methods of high entropy alloy coatings include magnetron sputtering, electrochemical deposition, thermal spraying, etc. The advantages of magnetron sputtering technology are mainly reflected in the fast film formation rate, good film adhesion and the ability to achieve large-area coating. The electrochemical deposition method has the advantages of a simple process and the ability to adjust the composition by changing the electrodeposition parameters. The thickness of the coating prepared by thermal spraying can reach tens of microns to hundreds of microns. However, the coatings prepared by these methods generally have defects such as pores, microcracks, inclusions, etc., have low bonding strength, and are prone to shedding, which in turn affects the wear resistance and high-temperature oxidation resistance of the coating.
[0005] In recent years, in order to further improve the hardness, wear resistance and high-temperature oxidation resistance of high-entropy alloys, researchers have begun to learn from traditional metals and introduce high-hardness, wear-resistant and high-temperature resistant ceramic phases into high-entropy alloys through the research ideas of ceramic-reinforced composites, in order to further improve their comprehensive performance. At present, the commonly used ceramic reinforcement phases mainly include Al2O3, TiC, TiB, WC, NbC, ZrC, etc., which are distributed in the coating by direct addition or in-situ self-generation. In-situ self-generated ceramic phases have many advantages, which make the coating have better performance and stability in application. In-situ self-generated ceramic phases can be introduced through methods such as magnetron sputtering, electrochemical deposition, and thermal spraying. However, due to the differences in thermophysical properties between the ceramic phase and the coating substrate, the introduction of ceramic reinforcement phases usually brings about some problems such as embrittlement and cracking of the coating, which further aggravates the problems of many coating defects, low bonding strength, and easy detachment in methods such as magnetron sputtering, electrochemical deposition, and thermal spraying, which in turn seriously affects the hardness, wear resistance, and high-temperature oxidation resistance of the coating, limiting the application of high-entropy alloy coatings in actual engineering. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace B, so as to solve the problems existing in the above-mentioned prior art.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] One of the technical solutions of the present invention is a method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B, comprising the following steps:
[0009] Al powder, Cr powder, Fe powder, Ti powder, V powder and B powder are uniformly mixed in a molar ratio of 1:1:1:1:1:0 to 0.1 to obtain powder for laser cladding; the powder for laser cladding is pre-placed on the surface of a titanium alloy substrate, and then laser cladding is performed to obtain the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with a trace amount of B; wherein the amount of B powder is not 0.
[0010] First, Al, Ti, and Cr will form an oxide film under high temperature conditions to improve the oxidation resistance of the high entropy alloy coating. In addition, the larger atomic radius of the Ti element will cause lattice distortion, thereby improving the strength and hardness of the high entropy alloy coating. The simultaneous addition of V and Cr can provide good antioxidant protection at different temperatures and enhance the wear resistance of the high entropy alloy coating. Finally, the presence of the Fe element can promote the formation of BCC solid solution. The components in the high entropy alloy coating obtained by the present invention using Al powder, Cr powder, Fe powder, Ti powder, and V powder as main raw materials work synergistically, so that the coating has higher hardness, wear resistance and high temperature oxidation resistance. In addition, during the laser cladding process, O and Al in the air can also generate Al2O3 ceramic phase in situ. Moreover, the present invention also dopes a trace amount of B (boron) into the high entropy alloy. The solid solubility of B in Ti is 0.05%, while that in Al is only 0.001%. Since the solid solubility of B in Ti is much higher than that in Al, after the introduction of the B element, B is more likely to occupy the gaps in Ti during the laser cladding process, thereby inhibiting the reaction between O and Ti, and further promoting the formation of the Al2O3 ceramic reinforcement phase. The increase in the Al2O3 ceramic reinforcement phase can improve the friction, wear and high-temperature oxidation resistance of the high-entropy alloy coating.
[0011] In addition, laser cladding is a green surface modification technology that uses a high-energy laser beam as a heat source to melt the metal powder raw material and rapidly solidify it to prepare a coating. During the laser cladding process, the laser energy density is high, and it can quickly melt refractory metal elements. The solidification rate of the metal liquid in the molten pool is fast, and fine tissue grains can be obtained. The alloy has no obvious component segregation, which is conducive to reducing coating defects, improving the bonding strength between the coating and the substrate, and reducing the embrittlement and cracking caused by the introduction of the ceramic reinforcement phase. In the present invention, the high entropy alloy material is metallurgically bonded to the titanium alloy substrate through laser cladding technology. The substrate and the cladding layer have good bonding strength, and the substrate has small thermal deformation and low dilution rate, which further improves the comprehensive performance of the high entropy alloy coating. In the present invention, the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace B obtained by combining a specific high entropy alloy material composition with a specific laser cladding process has excellent comprehensive properties (high hardness, high wear resistance and excellent high temperature oxidation resistance).
[0012] Furthermore, the titanium alloy substrate is a TC4 titanium alloy (Ti-6Al-4V) substrate.
[0013] The raw materials of the coating contain Ti, Al, and V present in the Ti-6Al-4V (TC4) substrate, which ensures that the coating is not contaminated by the substrate.
[0014] Furthermore, the molar ratio of the Al powder, Cr powder, Fe powder, Ti powder, V powder and B powder is preferably 1:1:1:1:1:0.05-0.1.
[0015] When the doping amount of B is lower than this range, the effect of promoting the formation of Al2O3 ceramic reinforcement phase is not good. When it is higher than this range, it may lead to increased brittleness, complex crystal structure and decreased processing performance.
[0016] Furthermore, the purity of the Al powder, Cr powder, Fe powder, Ti powder, V powder and B powder is not less than 99.95%, and the particle size is 45-75 μm.
[0017] Selecting metal powder within this particle size range as the raw material for laser cladding coating helps to obtain a uniform and dense coating.
[0018] Furthermore, the mixing is performed by ball milling; the rotation speed of the ball milling is 100 to 120 rpm, and the time is 2 to 6 hours.
[0019] Furthermore, after the ball milling is completed, a drying operation is also included; the drying temperature is 80° C. and the drying time is 10 to 12 hours.
[0020] Furthermore, the laser cladding is performed in a mixed atmosphere of protective gas and air.
[0021] Furthermore, the parameters of the laser cladding include: laser power of 600-800W, scanning speed of 200-400mm / min, spot diameter of 3-5mm, defocus of 210-230mm, and shielding gas of argon; the gas flow rate of the shielding gas is 14-16L / min, and the concentration in the mixed atmosphere is 70vol%.
[0022] Furthermore, before pre-placing the laser cladding powder on the surface of the titanium alloy substrate, the method further includes pre-treating the titanium alloy substrate, and the specific operations are: polishing, ultrasonic cleaning and drying the titanium alloy substrate in sequence.
[0023] The main purpose of grinding is to remove the oxide film, dirt and defects on the surface of the titanium alloy substrate, making the surface flat and smooth, thereby increasing the bonding area between the coating and the substrate and improving the bonding strength. In addition, grinding can also eliminate surface unevenness and defects, reducing the possibility of cracks in the coating during the cladding process. Ultrasonic cleaning can further remove impurities and oil stains remaining after grinding to ensure that the surface of the substrate is clean and pollution-free. This helps to reduce the problem of poor bonding between the coating and the substrate caused by impurities and ensure the uniformity and density of the coating. Ultrasonic cleaning can also destroy the gas and liquid films adsorbed on the surface of the substrate and reduce the generation of bubbles during the coating preparation process. In summary, the above pretreatment helps to ensure the bonding between the coating and the substrate and the quality of the coating.
[0024] The second technical solution of the present invention: a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B prepared according to the above preparation method.
[0025] Furthermore, the coating has a thickness of 1.0 to 1.5 mm.
[0026] The present invention discloses the following technical effects:
[0027] The high entropy alloy coating obtained by laser cladding and doping with trace amounts of B in the present invention has good macroscopic morphology (few defects) and achieves good metallurgical bonding between the coating and the substrate. The coating also has the characteristics of high hardness, excellent wear resistance, high-temperature oxidation resistance, etc.
[0028] The present invention improves the inherent friction and wear and poor high-temperature oxidation resistance of titanium alloys by preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high-entropy alloy coating doped with trace amounts of B on the surface of titanium alloy, which has a positive effect on promoting the practical engineering applications of titanium alloys in extreme environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a surface morphology of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating prepared in Example 2;
[0031] Figure 2 Surface XRD patterns of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coatings prepared in Examples 1 to 2 and Comparative Example 1;
[0032] Figure 3 This is a cross-sectional SEM image of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating prepared in Comparative Example 1;
[0033] Figure 4 This is a cross-sectional SEM image of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating prepared in Example 1;
[0034] Figure 5 This is a cross-sectional SEM image of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating prepared in Example 2;
[0035] Figure 6The microhardness trend diagram of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating prepared in Examples 1 to 2 and Comparative Example 1;
[0036] Figure 7 The wear rate trend diagram of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating and TC4 substrate prepared in Examples 1-2 and Comparative Example 1;
[0037] Figure 8 This is an oxidation kinetics curve of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating prepared in Examples 1 to 2 and Comparative Example 1 and the TC4 substrate oxidized at 900°C for 50 hours. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] The present invention provides a method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with a trace amount of B, comprising the following steps:
[0044] Al powder, Cr powder, Fe powder, Ti powder, V powder and B powder are mixed in a molar ratio of 1:1:1:1:1:0-0.1, and ball milled to obtain powder for laser cladding; the powder for laser cladding is laid in strips on the surface of a titanium alloy substrate to form a strip-shaped pre-deposited layer, and then laser cladding is performed (i.e., the titanium alloy substrate and the pre-deposited layer are melted together through a laser cladding system, and a high-entropy alloy coating is prepared on the surface of the titanium alloy by the action of a high-energy laser beam) to obtain the laser cladding in-situ self-generated Al2O3 ceramic reinforced high-entropy alloy coating doped with trace amounts of B.
[0045] As a preferred embodiment of the present invention, the titanium alloy substrate is a TC4 titanium alloy substrate.
[0046] As a preferred embodiment of the present invention, the molar ratio of the Al powder, Cr powder, Fe powder, Ti powder, V powder and B powder is 1:1:1:1:1:0.05-0.1.
[0047] As a preferred embodiment of the present invention, the purity of the Al powder, Cr powder, Fe powder, Ti powder, V powder and B powder is not less than 99.95%, and the particle size is 45-75 μm.
[0048] As a preferred embodiment of the present invention, the rotation speed of the ball mill is 100-120 rpm, and the time is 2-6 hours.
[0049] As a preferred embodiment of the present invention, the ball-to-material ratio of the ball mill is 4:1.
[0050] As a preferred embodiment of the present invention, the ball milling further includes a drying operation; the drying temperature is 80° C. and the drying time is 10 to 12 hours; the drying is specifically vacuum drying.
[0051] As a preferred embodiment of the present invention, the laser cladding is performed in a mixed atmosphere of protective gas and air.
[0052] As a preferred embodiment of the present invention, the parameters of the laser cladding include: laser power of 600-800 W, scanning speed of 200-400 mm / min, spot diameter of 3-5 mm, defocusing amount of 210-230 mm, and shielding gas of argon; the gas flow rate of the shielding gas is 14-16 L / min, and the concentration in the mixed atmosphere is 70 vol%.
[0053] As a preferred embodiment of the present invention, before pre-placing the laser cladding powder on the surface of the titanium alloy substrate, the method further includes pre-treating the titanium alloy substrate, specifically, grinding, ultrasonically cleaning and drying the titanium alloy substrate in sequence.
[0054] As a preferred embodiment of the present invention, the polishing is specifically polishing with 200 mesh and 350 mesh sandpaper in sequence; the ultrasonic cleaning is specifically ultrasonic cleaning in anhydrous ethanol; the drying temperature is 60-80°C and the drying time is 2-3h.
[0055] The present invention also provides a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B prepared according to the above preparation method.
[0056] As a preferred embodiment of the present invention, the thickness of the coating is 1.0 to 1.5 mm.
[0057] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0058] The room temperature involved in the specific implementation manner of the present invention specifically refers to 20-30°C.
[0059] The purity of Al powder, Cr powder, Fe powder, Ti powder, V powder and B powder used in the following examples and comparative examples is not less than 99.95%, and the particle size is 45-75 μm.
[0060] The size of the TC4 titanium alloy substrate used in the following examples and comparative examples is 40 mm×14 mm×4 mm.
[0061] Example 1
[0062] A method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace B, the steps are as follows:
[0063] (1) Six metal powders of Al, Cr, Fe, Ti, V and B were weighed in a molar ratio of 1:1:1:1:1:0.05 and placed in a ball mill for high-energy ball milling. A grinding ball with a diameter of 5 mm was used (the ball mill jar and grinding balls were made of stainless steel), a ball-to-material ratio of 4:1, a ball milling time of 4 h, a ball mill speed of 100 r / min, and the mixture was allowed to stand for 3 h to room temperature to obtain a mixed metal powder.
[0064] (2) The mixed metal powder after ball milling is placed in a drying oven for drying to obtain powder for laser cladding; the drying temperature is 80° C. and the drying time is 10 h.
[0065] (3) The TC4 titanium alloy substrate is pretreated. The specific operation of the pretreatment is as follows: the TC4 titanium alloy is polished with 200 mesh and 350 mesh metallographic sandpaper in sequence until the surface is flat and smooth to remove the surface oxide film, dirt and defects, thereby reducing the reflection of the substrate surface to the laser. The polished TC4 titanium alloy substrate is rinsed with clean water and ultrasonically cleaned in anhydrous ethanol for 5 minutes to remove the remaining oil and impurities on the surface; after cleaning, it is placed in a drying oven at 80°C for 2 hours.
[0066] (4) Pre-depositing the powder for laser cladding on the surface of the pretreated TC4 titanium alloy substrate. Specifically, the powder for laser cladding is laid on the surface of the TC4 titanium alloy substrate in strips to form a strip-shaped pre-deposited layer.
[0067] (5) Laser cladding was performed to obtain an in-situ Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B (the thickness of the coating was regulated by controlling the amount of powder used for laser cladding, and ultimately a coating with a thickness of 1.5 mm was obtained); the laser power was 700 W, the scanning speed was 300 mm / min, the spot diameter was 3 mm, the defocus amount was 220 mm, and the laser cladding was performed in a mixed atmosphere of a protective gas and air. Argon was used as the protective gas, and the gas flow rate was 15 L / min. The concentration of argon in the mixed atmosphere was controlled to be 70 vol%.
[0068] Example 2
[0069] The same as Example 1, except that six metal powders of Al, Cr, Fe, Ti, V and B are weighed as raw materials in a molar ratio of 1:1:1:1:1:0.1.
[0070] Comparative Example 1
[0071] The same as Example 1, except that five metal powders of Al, Cr, Fe, Ti and V are weighed as raw materials at a molar ratio of 1:1:1:1:1, that is, trace doping of B is omitted.
[0072] Test Case
[0073] The morphology of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating prepared in Example 2 was analyzed. Figure 1 This is the surface morphology of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating prepared in Example 2. Figure 1 It can be seen that the high entropy alloy material achieves metallurgical bonding with the titanium alloy substrate through laser cladding technology. The substrate and the cladding layer have good bonding strength, and the substrate has small thermal deformation and low dilution rate.
[0074] Phase analysis was performed on the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coatings prepared in Examples 1 to 2 and Comparative Example 1. The XRD diffraction patterns of the coatings prepared in Examples 1 to 2 and Comparative Example 1 are as follows: Figure 2 As shown. Figure 2 It can be seen that the phase structures of the three are composed of BCC phase, TiO2 phase, Al2O3 phase and Laves phase (intermetallic compound). After adding a trace amount of B, the TiO2 phase in the coating gradually decreases, while the Al2O3 phase increases and the Laves phase also decreases. This change is related to the adjustment of the crystal structure and chemical composition caused by the introduction of the B element.
[0075] The cross-sectional microstructure of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating prepared in Examples 1 to 2 and Comparative Example 1 was observed. Before the test, the cross-sectional surface of the sample was polished with 180 mesh, 400 mesh, 800 mesh, and 1200 mesh sandpaper in stages until the surface became flat and free of obvious scratches. After polishing, the sample was cleaned with anhydrous ethanol and clean water, and dried with a hair dryer to obtain a sample that can be used to observe the microstructure. The cross-sectional morphology of the coating in Examples 1 to 2 and Comparative Example 1 is shown in FIG. Figures 3 to 5 As shown ( Figure 3 For comparative example 1, Figure 4 For Example 1, Figure 5 Example 2). By observing the images, it can be clearly seen that there are mainly two phases with different structures in each coating: BCC phase and oxide phase, and a small amount of Laves phase. Among them, the BCC phase is presented as a white area in the figure, and the dark gray precipitate phase corresponds to TiO2 and Al2O3 phases. And as the B content increases, the cracks and pores of the coating gradually decrease.
[0076] The hardness of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coatings prepared in Examples 1 to 2 and Comparative Example 1 was measured using a microhardness tester. The hardness variation trend was as follows: Figure 6 As shown (where AlCrFeTiV represents comparative example 1, B 0.5at.% represents example 1, and B 1.0at.% represents example 2). It can be seen that with the increase of B content, the hardness of the coating is significantly improved. This result is due to the effects of two main aspects. On the one hand, B atoms will occupy the interstitial position of BCC, dissolve in BCC, and form interstitial solid solution, thereby playing a role of solid solution strengthening. On the other hand, with the increase of B content in the coating, the content of Al2O3 ceramic phase in the coating also increases. As a high-hardness ceramic phase, Al2O3 plays the role of second-phase pinning strengthening in the coating, effectively enhancing the hardness of the coating.
[0077] The friction performance of the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating and TC4 substrate prepared in Examples 1 to 2 and Comparative Example 1 was measured using a reciprocating friction and wear tester (UMT-2). The wear rate trend graph obtained is as follows: Figure 7 As shown (TC4 represents the substrate, B0 represents comparative example 1, B 0.5 represents example 1, and B 1.0 represents example 2). It can be seen that the wear resistance of B0, B0.5 and B1.0 coatings is 1.21 times, 2.36 times and 3.71 times higher than that of the TC4 substrate, respectively, and the HEA coating containing 1.0 at.% B has the lowest wear rate. This is because as the B content added to the coating increases, the Al2O3 ceramic phase content increases, resulting in improved wear resistance of the coating. This experimental result shows that the coating obtained by adding different amounts of B to the AlCrFeTiV high entropy alloy system can effectively improve the hardness and friction and wear properties of the TC4 titanium alloy.
[0078] The laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coatings and TC4 substrates prepared in Examples 1-2 and Comparative Example 1 were subjected to constant temperature (900°C) oxidation in air for 50 hours. The oxidation kinetic curves are shown in Figure 2. Figure 8 As shown (where Ti-6Al-4V alloy represents TC4 substrate, AlCrFeTiV represents comparative example 1, AlCrFeTiVB 0.5 Representative Example 1, AlCrFeTiVB 1.0 Representative Example 2). It can be seen from the curve that compared with the TC4 substrate, the oxidation weight gain of the three coatings is significantly lower than that of the TC4 substrate, and the oxidation weight gain of Example 1 and Example 2 with added B is lower than that of Comparative Example 1 without added B. This means that after adding an appropriate amount of element B, the high-temperature oxidation resistance of the high-entropy alloy coating is significantly improved. This performance improvement may be attributed to the fact that element B can promote the formation of Al2O3, thereby increasing the surface density of the coating, effectively preventing the diffusion of oxygen, and slowing down the oxidation rate of the coating.
[0079] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B, characterized in that: The following steps are involved: Al powder, Cr powder, Fe powder, Ti powder, V powder and B powder are uniformly mixed in a molar ratio of 1:1:1:1:1:0 to 0.1 to obtain powder for laser cladding; the powder for laser cladding is pre-placed on the surface of a titanium alloy substrate, and then laser cladding is performed to obtain the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with a trace amount of B; wherein the amount of B powder is not 0.
2. The method for preparing the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B as claimed in claim 1, characterized in that: The titanium alloy substrate is a TC4 titanium alloy substrate.
3. The method for preparing the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B as claimed in claim 1, characterized in that: The purity of the Al powder, Cr powder, Fe powder, Ti powder, V powder and B powder is not less than 99.95%, and the particle size is 45-75 μm.
4. The method for preparing the laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B as claimed in claim 1, characterized in that: The mixing is performed by ball milling; the rotation speed of the ball milling is 100 to 120 rpm, and the time is 2 to 6 hours.
5. The method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B as claimed in claim 4, characterized in that: After the ball milling is completed, a drying operation is also included; the drying temperature is 80° C. and the drying time is 10 to 12 hours.
6. The method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B as claimed in claim 1, characterized in that: The laser cladding is performed in a mixed atmosphere of protective gas and air.
7. The method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B as claimed in claim 6, characterized in that: The parameters of the laser cladding include: laser power of 600-800W, scanning speed of 200-400mm / min, spot diameter of 3-5mm, defocusing amount of 210-230mm, and shielding gas of argon; the gas flow rate of the shielding gas is 14-16L / min, and the concentration of the shielding gas in the mixed atmosphere is 70vol%.
8. The method for preparing a laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B as claimed in claim 1, characterized in that: Before pre-placing the laser cladding powder on the surface of the titanium alloy substrate, the titanium alloy substrate is also pre-treated, and the specific operations are: polishing, ultrasonic cleaning and drying the titanium alloy substrate in sequence.
9. A laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B prepared by the preparation method according to any one of claims 1 to 8.
10. The laser cladding in-situ self-generated Al2O3 ceramic reinforced high entropy alloy coating doped with trace amounts of B as claimed in claim 9, characterized in that: The thickness of the coating is 1.0-1.5 mm.
Citation Information
Patent Citations
In-situ synthesis Al2O3 enhanced high-entropy alloy coating and preparation method
CN116200739A
Cited By
Preparation method of titanium alloy pipe
CN121228235A